Forming the productivity of winter wheat varieties under the influence of humic substances - Маренич, М. М.; Юрченко, С. О.; Баган, А. В.; Єщенко, В. М. (Scientific Progress & Innovations, 2018)
The article discusses the features of the use of growth stimulators by Soil-Biotics (USA) as an example of the integrated use of humates to improve the yield of winter wheat. It is proved that the norms and methods of using humates for presowing seed treatment and introduction into the soil contribute to a better formation of the elements of the yield structure, primarily productive tillering. Statistical processing by the method of multivariate analysis of variance showed that the variants in which presowing seed treatment with 1R Seed treatment was applied at a rate of 3 kg / t and applied to the soil 5R SoilBoost EA in the norm of 30 kg / ha, significantly exceeded the control by the number of plants , which were better wintered and productive. Analysis of the effect of humic preparations on the formation of signs of productivity shows that as a result of presowing seed treatment and application of humic preparation 5R SoilBoost EA during sowing, productive tillering increases by almost 37%. Other signs respond to the use of drugs less - the number of grains in the ear increased by 7.3%, and the mass of grain from the ear - by 5.5%. However, this difference was statistically significant compared to the control options. The mass of 1000 grains remained virtually unchanged - there was no statistically significant difference between the variants.